Literacy and Sexuality: What's the Connection? - Ashcraft, Catherine (Journal of adolescent & adult literacy, 2009)
In this column, the author highlights how the current framing of teen sexuality obscures important connections between literacy and sexuality. She argues that we need to challenge two current assumptions: the assumption that teen sexuality is primarily about public health and the assumption that all efforts to address teen sexuality are necessarily “controversial.” Challenging these assumptions is particularly important for literacy educators who truly believe that identity is integral to youth's literacy development. Perhaps, now more than ever, we cannot afford to behave as if this conceptualization somehow excludes sexual identity. Moving beyond these current frames opens up innovative possibilities for connecting with youth and for using teen interest in sexuality as a vehicle for students' literacy development and academic success. في هذه المقالة تبرز المؤلفة كيف التأطير الحالي لمظاهر الأنوثة أو الرجولة تابعة للمراهقين يُبهِم روابط هامة بين التعلم ومظاهر الجنس. وعليه فتقدم المؤلفة الحجة بأن لا بد لنا من أن نتحدى افتراضين متداولين في الوقت الحاضر: الافتراض الأول متعلق بمظاهر الأنوثة أو الرجولة لدى المراهقين يقول إنه هو بأساسه قضية الصحة العامة والافتراض الثاني يزعم أن كل الجهود المبذولة لتتعامل مع مظاهر الجنس هي بضرورة ((مثيرة للجدل)). إن القيام بتحدي هذين الافتراضين هام جداً خصوصاً لمعلمي معرفة القراءة والكتابة الذين يؤمنون بأن الهوية أمر جوهري لتنمية معرفة القراءة والكتابة لدى الشباب. لعل، الآن أكثر من الوقت سابق، لا نستطيع أن نتصرف كأن هذا التخيل يستثني الهوية الجنسية بطريقة أو بأخرى. وإذا تجاوزنا هذه الإطارات فستفتح احتمالات مبدعة لاتصال بالشباب وأيضاً لاستخدام اهتمام المراهقين بالمظاهر الجنسية كوسيلة لتنمية معرفة القراءة والكتابة لدى الطلاب ونجاحهم الدراسي. 作者在这专栏里，让读者注意到当前对青少年性意识这问题所采用的表达方式，如何掩盖读写文化和性意识之间的重要关联。作者认为，我们需要对两个流行的假设提出质疑：青少年性意识主要是关于公共卫生这个假设，及所有为解决青少年性意识问题而作出的努力必然是「具有争议性」这个假设。对于真正相信身份认同是青少年读写能力发展的重要部分的教育家来说，向这两个假设提出质疑尤其重要。或许，在性意识的概念形成上，我们不应再象过去那样，把性身份认同置之不理。超越当前对青少年性意识这问题所采用的表达方式，我们可以开启创新的机会，与青年人联系起来，并可以善用青少年对性意识的兴趣，引领学生通往读写能力发展和学术成功之路。 Dans cette rubrique, l'auteur met en évidence de quelle façon l'encadrement actuel de la sexualité des jeunes occulte les liens importants entre littératie et sexualité. Elle estime qu'il faut mettre en question deux positions courantes: la position selon laquelle la sexualité des jeunes concerne d'abord la santé publique et la position selon laquelle tous les efforts concernant la sexualité des jeunes sont nécessairement « polémiques ». Mettre en question ces positions est particulièrement important pour les enseignants de littératie qui croient vraiment que l'identité est partie intégrante du développement de la littératie des jeunes. Peut‐être, maintenant plus que jamais, ne pouvons‐nous pas nous permettre de faire comme si cette conception excluait en quelque sorte la sexualité. Dépasser ces cadres habituels ouvre à des possibilités créatives d'établir des liens avec les jeunes et d'utiliser l'intérêt qu'ils portent à la sexualité comme moyen pour développer la littératie des élèves et leur réussite scolaire. В этом выпуске рубрики автор обсуждает, как общепринятое восприятие сексуальности подростков мешает выявлению важных связей между грамотностью и сексуальностью. Необходимо бросить вызов двум расхожим идеям, первая из которых состоит в том, что сексуальность подростков должна быть связана, прежде всего, с охраной их здоровья, а вторая утверждает, что любые усилия в области сексуальности подростков непременно являются “спорными”. Для педагогов, занимающихся развитием грамотности и искренне полагающих, что становление самоидентичности неразрывно связано с развитием грамотности, особенно важно оспорить эти идеи. Возможно, сейчас – больше чем когда‐либо – мы не можем позволять себе вести себя так, будто становление личного “я” исключает становление сексуальной самоидентичности. Уход от этих привычных фреймов открывает педагогам новые возможности для установления контакта с молодежью и для использования интереса подростков к сексуальности как рычага при развитии их грамотности и стимулировании их академического роста. En esta columna, la autora hace resaltar cómo la manera en que se enmarca hoy día la sexualidad adolescente no nos permite ver claramente las conexiones importantes entre el aprendizaje y la sexualidad. La autora mantiene que debemos cuestionar dos suposiciones: que la sexualidad adolescente es primordialmente un problema de salud pública, y que todos los esfuerzos de abordar el tema de la sexualidad adolescente son necesariamente “controvertidos”. Desafiar estas suposiciones es especialmente importante para los educadores de aprendizaje que realmente creen que la identidad es integral al desarrollo del aprendizaje de los jóvenes. A lo mejor, hoy más que nunca, no podemos permitirnos el lujo de portarnos como si este concepto excluyera la identidad sexual. Ir más allá de estos marcos abre nuevas posibilidades para conectar con los jóvenes y para usar el interés de los jóvenes en su sexualidad como un vehículo para el desarrollo del aprendizaje y su éxito académico.